2020
DOI: 10.1063/5.0014347
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced lattice expansion and phonon softening in layered ReS2

Abstract: We report high pressure x-ray diffraction and systematic Raman measurements on a ReS 2 sample, which is mechanically exfoliated from a single crystal. A few new Bragg peaks are observed to emerge above 6 GPa indicating a structural transition from distorted 1T to distorted 1T 0 in a triclinic structure. The same is corroborated by the appearance of new Raman modes in the same pressure range. Softening of the Raman modes corresponding to Re atom vibrations is observed in the distorted 1T 0 phase in the pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
3
19
1
Order By: Relevance
“…A fit with a 3rd-order BM EoS (BM-3) yields a zero-pressure bulk modulus B 0 = 44(2) GPa, with a first derivative equal to B' = 7.7 (5). The value for B 0 is in excellent agreement with recent experimental results for this compound [23] and, as will be explained below, also with our own experimental determinations. However, a careful analysis of the normalized pressure (F) vs. strain curves (f ) that result from the theoretical P-V dependence obtained with PBE+D3 (see Figure S2a,b) suggests that a 4th-order BM EoS (BM-4) provides the best fit along the whole pressure range.…”
Section: T-res 2 and Re 1−x Mo X S 2 Under Pressuresupporting
confidence: 91%
See 4 more Smart Citations
“…A fit with a 3rd-order BM EoS (BM-3) yields a zero-pressure bulk modulus B 0 = 44(2) GPa, with a first derivative equal to B' = 7.7 (5). The value for B 0 is in excellent agreement with recent experimental results for this compound [23] and, as will be explained below, also with our own experimental determinations. However, a careful analysis of the normalized pressure (F) vs. strain curves (f ) that result from the theoretical P-V dependence obtained with PBE+D3 (see Figure S2a,b) suggests that a 4th-order BM EoS (BM-4) provides the best fit along the whole pressure range.…”
Section: T-res 2 and Re 1−x Mo X S 2 Under Pressuresupporting
confidence: 91%
“…If, instead, a BM-3 EoS is employed together with the B' = 7.7 value obtained from the DFT calculations, which is still found to reasonably match the F-f dependence ( Figure S2d), the following results are obtained: V 0 = 217.9(2) Å 3 and B 0 = 46(2) GPa. These values are in excellent agreement with the PBE+D3 calculations (BM-3 fit, see Table 1) and also with the recent work by Saha et al [23], who reported a similar experimental bulk modulus (B 0 = 44(2) GPa), although with a much lower first derivative (B' = 1.6(3)). In contrast, other previous works reported much lower B 0 values of 23 GPa [21] and 35.6 GPa [22].…”
Section: High-pressure Xrd Of 1t-ressupporting
confidence: 91%
See 3 more Smart Citations